2004
DOI: 10.1111/j.1526-4610.2004.04124.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Use of Triptans and Reasons for Switching Them in a Tertiary Care Migraine Population

Abstract: A variety of treatment attributes are important in determining the reasons involved in switching a triptan. To assess this attributes can provide additional information to supplement the traditional tests of efficacy provided by randomized clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 14 publications
3
63
0
Order By: Relevance
“…Two studies showed that more patients preferred oral sumatriptan 50 or 100 mg than other oral triptans [11,31,32]. Two studies showed few differences between several oral triptans [33,34], and a further study showed that patients preferred zolmitriptan nasal spray over oral triptans [35]. Different study designs and the patients' initial triptan may have biased the results from these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies showed that more patients preferred oral sumatriptan 50 or 100 mg than other oral triptans [11,31,32]. Two studies showed few differences between several oral triptans [33,34], and a further study showed that patients preferred zolmitriptan nasal spray over oral triptans [35]. Different study designs and the patients' initial triptan may have biased the results from these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective review of 386 patients who used subcutaneous sumatriptan and were switched to a different triptan or formulation, 19.5% returned to subcutaneous sumatriptan [34]. For the other triptans/formulations, the percentages for returning were: sumatriptan 25 mg, 7.8%; sumatriptan 50 or 100 mg, 42.3%; sumatriptan nasal spray, 17.7%; zolmitriptan, 17.6%; rizatriptan, 16.5%; naratriptan, 9.4%.…”
Section: Multiple Comparisons Between the Triptansmentioning
confidence: 99%
“…Sheftell et al [10] reported that patients receiving rizatriptan experience switching to other drugs least frequently. Ninan et al [11] reported that the pain-free rate in migraine patients receiving rizatriptan at an early stage was significantly higher than those for patients receiving other triptans.…”
Section: Discussionmentioning
confidence: 99%
“…The first triptan introduced in the USA was sumatriptan in a 6-mg subcutaneous (SC) injection. There are currently seven triptans available in the USA with several formulations available for delivery including oral tablets, orally disintegrating tablets, nasal sprays and SC injection [3].…”
Section: Introductionmentioning
confidence: 99%